Dampak Pola Asuh Orang Tua Buruh Pabrik Terhadap Kecerdasan Spiritual Anak di Desa Wonosari Kecamatan Wonorejo - Achmat Mubarok; Ibnu Athoillah, Muhammad; Mahbubah, Saniatul (AL MURABBI, 2022)
The family environment is the first place for children to develop their education and intelligence, especially spiritual intelligence. The assumption of society is that parents who work as factory workers have little time to care for and interact with their children so that spiritual intelligence is considered less well-achieved. The purpose of this study was (1) to determine the form of parenting pattern for factory workers in Wonosari Village (2) to determine the impact of factory worker parenting on the spiritual intelligence of children in Wonosari Village. The approach used by researchers in this study is a qualitative approach that produces descriptive data. The type of research used is Natural setting. The results of the study are that there are 3 types of parenting styles in Wonosari Village, namely (1) Authoritarian, namely the type of parenting that makes parents the center of child control (2) Democratic, namely the type of parenting in which parents provide space for children to control and do what he wants but still with parental consent. (3) Permissive, namely parents who do not care and are reluctant to control their children. The impact of authoritarian parenting patterns on children's spiritual intelligence is the impact of spiritual intelligence from the form of parents with authoritarian parenting patterns that are slightly weak, because of the pressure and limitations of thinking that hinder the development of spiritual intelligence. The impact of spiritual intelligence from the democratic form of parenting is good because parents fully support the child's potential and the impact of spiritual intelligence of children from the permissive form of parenting is very weak because parents do not care about the child's condition.